2023
DOI: 10.3390/v15061339
|View full text |Cite
|
Sign up to set email alerts
|

Roles and Mechanisms of NLRP3 in Influenza Viral Infection

Abstract: Pathogenic viral infection represents a major challenge to human health. Due to the vast mucosal surface of respiratory tract exposed to the environment, host defense against influenza viruses has perpetually been a considerable challenge. Inflammasomes serve as vital components of the host innate immune system and play a crucial role in responding to viral infections. To cope with influenza viral infection, the host employs inflammasomes and symbiotic microbiota to confer effective protection at the mucosal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 179 publications
0
3
0
Order By: Relevance
“…The human gut microbiota consists of approximately 10 14 microorganisms and plays a crucial role in host function, especially in immunity and metabolism ( Tao et al., 2022 ; Niu and Meng, 2023 ). Many studies demonstrated that the gut microbiota is closely interrelated with GBC progression, but most relative mechanistic studies have primarily focused on bacteria.…”
Section: Bacteria In Gbc Pathogenesismentioning
confidence: 99%
“…The human gut microbiota consists of approximately 10 14 microorganisms and plays a crucial role in host function, especially in immunity and metabolism ( Tao et al., 2022 ; Niu and Meng, 2023 ). Many studies demonstrated that the gut microbiota is closely interrelated with GBC progression, but most relative mechanistic studies have primarily focused on bacteria.…”
Section: Bacteria In Gbc Pathogenesismentioning
confidence: 99%
“…Influenza virus infection is a significant example; the activation of the NLRP3 inflammasome is closely related to the immune response. In the early stages of IAV infection (the first five days after infection), the activation of NLRP3 triggers the release of inflammatory factors such as IL-1 β and IL-18, which help recruit immune cells and improve their ability to fight the virus [ 15 ]. Cytomegalovirus infection also shows signs that NLRP3 may play an antiviral effect.…”
Section: Activation Of Nlrp3mentioning
confidence: 99%
“…After influenza virus invasion, viral ribonucleoproteins are released into the nucleus for transcription and replication. SsRNA is recognized by TLR7 and triggers the expression of NF-kB, pro-IL-1b, pro-IL-18, and other proinflammatory cytokines (Niu and Meng, 2023). Studies have shown a lack of IL-1b release by infecting influenza virus into TLR7-deficient bone marrow-derived DCs (Ichinohe et al, 2010).…”
Section: Influenza Virus Infection and Nlrp3 Inflammasomementioning
confidence: 99%